APPLYING A GENRE BASED-APPROACH WITH AUDIO VISUAL AID FOR IMPROVING WRITING SKILL IN GRADE 11 STUDENTSOF MADRASAH ALIYAH NEGERI SERDANG BEDAGAI - Herlina Herlina; yulia arfanti (Universitas Negeri Medan, 2023)
Abstract : APPLYING A GENRE BASED-APPROACH WITH AUDIO VISUAL AID FOR IMPROVING WRITING SKILL IN GRADE 11 STUDENTSOF MADRASAH ALIYAH NEGERI SERDANG BEDAGAI. The purpose of this study is To find out the effectiveness in applying a GBA with Audio Visual Media in Teaching Listening for improving writing skill in Grade 11 students in MANSB. The Subject of study was all of the 11th grade students of MANSB. This research procedure include is: Preparing a GBA learning model; Determining the class/treatment group, namely the control group and experimental group, Doing pre test, Conducting teaching and learning activities (KBM) in the experimental class and control class using GBA learning model, Doing Post-test, and Analyzing the data. The Result of study in the experiment class (Pre-Test) is 36 students, the majority of the them (11 students or 31%) get the core in the range of 52.51-60.00. and in the control class (Pre-Test) is 35 students, the majority of the students (13 students or 37%) get the score in the range of 50.01 - 60.00. The Result of study in the experiment class (Post-Test) is 36 students, the majority of the them (8 students or 22%) get the core in the range of 82.51 - 88.33. and in the control class (Post-Test) is 35 students, the majority of the students (12 students or 34%) get the score in the range of 62.51 - 70.00.